2020
DOI: 10.1103/physreve.102.022901
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of contact friction and particle shape on strength properties and microstructure of sheared granular media

Abstract: We present a systematic numerical investigation concerning the combined effects of sliding friction and particle shape (i.e., angularity) parameters on the shear strength and microstructure of granular packings. Sliding friction at contacts varied from 0 (frictionless particles) to 0.7, and the particles were irregular polygons with an increasing number of sides, ranging from triangles to disks. We find that the effect of local friction on shear strength follows the same trend for all shapes. Strength first in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…The shear strength first increases for all shapes, but it may decline, saturate or continue to increase at larger angularity depending on the value of the local friction. This behavior is rather unexpected, and suggests a complex interplay at the microscopic scale [30]. Furthermore, our numerical results clearly highlight that attempting to represent noncircular/non-spherical shapes by hindering the rotations in assemblies of circular/spherical particles [31,32] must be reconsidered.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The shear strength first increases for all shapes, but it may decline, saturate or continue to increase at larger angularity depending on the value of the local friction. This behavior is rather unexpected, and suggests a complex interplay at the microscopic scale [30]. Furthermore, our numerical results clearly highlight that attempting to represent noncircular/non-spherical shapes by hindering the rotations in assemblies of circular/spherical particles [31,32] must be reconsidered.…”
Section: Discussionmentioning
confidence: 71%
“…Each numerical sample is composed of 10 000 particles, geometrically deposed and randomly oriented in a rectangular box with frictonnless walls. We prepare 11 packings, each of them composed of particles having the same number of sides n s : one packing of disks and 10 packings with n s ∈ [50, 30,20,10,8,7,6,5,4,3]. In addition, shape properties were described by the angularity, α = 2π/n s .…”
Section: Numerical Setupmentioning
confidence: 99%
“…Granular friction is vital to the ubiquitous packing and flow phenomena in nature and industrial production, such as geographical faults [1,2], powder mixing and densification [3], and granular flow lubrication [4,5]. The coefficient of friction (COF) is expressed as the tangential friction force divided by the total normal force and is typically used to describe the shear strength of a granular system [6][7][8][9]. Currently, granular friction research is associated with two experimental schemes, as follows: (1) the surface-sliding scheme, where the shearing unit is sliding against the surface of the granular system [10][11][12][13][14][15]; (2) the inside-sliding scheme, where the shearing unit is sliding inside the granular system [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of granular media composed of grains of a variety of shapes have shown that non-spherical/noncircular grains, which feature additional rotational resistance at the grain-grain interaction scale [9] , better represent measurable bulk parameters like shear strength [10][11][12][13], relative viscosity [14] in sheared suspensions, and jamming packing fraction [15] observed in real systems.…”
Section: Introductionmentioning
confidence: 99%